2017
DOI: 10.1016/j.ijmedinf.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

The role of computerized diagnostic proposals in the interpretation of the 12-lead electrocardiogram by cardiology and non-cardiology fellows

Abstract: Diagnostic proposals affect the diagnostic accuracy of ECG interpretations. The accuracy is significantly influenced especially when a single diagnostic proposal (either correct or incorrect) is provided. The study suggests that the presentation of multiple computerized diagnoses is likely to improve the diagnostic accuracy of interpreters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…However, these findings have been limited to single-lead ECGs 12 or fall short in providing complete 12-lead ECG interpretation. 13,14 Our AI-ECG algorithm is capable of comprehensive 12-lead ECG interpretation consistent with those provided by board-certified cardiologists on nearly 2.5 million standard 12-lead ECGs from over 720,000 adult patients. In recent work, we demonstrated that an AI-ECG algorithm could generate 66 structured diagnostic codes from a spectrum of uncommon and complex to normal ECG features (eg, primary and secondary rhythms, axis deviation, chamber enlargement/hypertrophy, atrioventricular and intraventricular conduction delay, myocardial ischemia, waveform abnormalities, clinical disorders, and pacemaker activity).…”
Section: Clinical Valuementioning
confidence: 82%
“…However, these findings have been limited to single-lead ECGs 12 or fall short in providing complete 12-lead ECG interpretation. 13,14 Our AI-ECG algorithm is capable of comprehensive 12-lead ECG interpretation consistent with those provided by board-certified cardiologists on nearly 2.5 million standard 12-lead ECGs from over 720,000 adult patients. In recent work, we demonstrated that an AI-ECG algorithm could generate 66 structured diagnostic codes from a spectrum of uncommon and complex to normal ECG features (eg, primary and secondary rhythms, axis deviation, chamber enlargement/hypertrophy, atrioventricular and intraventricular conduction delay, myocardial ischemia, waveform abnormalities, clinical disorders, and pacemaker activity).…”
Section: Clinical Valuementioning
confidence: 82%
“…It helps the experienced over-reader inadvertently avoid missing diagnoses and it improves the less experienced reader's performance. This was nicely documented by Novotny, et al [6], who demonstrated that diagnostic prompting improved interpretive accuracy substantially by both cardiology and non-cardiology fellows. For example, when multiple correct and incorrect diagnostic statements were presented, the over-readers were able to distinguish well between correct and incorrect statements, and they improved their diagnostic accuracy over their interpretations without availability of automated diagnostic statements by approximately 30%…”
Section: Automated Ecg Interpretation Is Beneficial Even In Major Hosmentioning
confidence: 67%
“…They also showed that the general practitioner using prompting from interpretive software further improved his/her detection of AF (92% sensitivity and 91% specificity). 6 Reader prompting is one of the greatest benefits of algorithmic interpretation. It helps the experienced over-reader inadvertently avoid missing diagnoses and it improves the less experienced reader's performance.…”
Section: Automated Ecg Interpretation Is Beneficial Even In Major Hosmentioning
confidence: 99%
“…When they are accurate, they have been shown to increase the accuracy of physician overread, but when inaccurate, they have been shown to lead physicians astray. This has been shown for cardiology fellows [15], for emergency physicians [16], and also for fully trained cardiologists, for whom the presence of an automated interpretation resulted in lower accuracy because automated errors were not corrected [17].…”
Section: Discussionmentioning
confidence: 94%